2015
DOI: 10.17795/ijpbs956
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acceptance and Commitment Therapy on Perceived Stress and Special Health Self-Efficacy in Seven to Fifteen-Year-Old Children With Diabetes Mellitus

Abstract: Background:Diabetes Mellitus (DM) imposes restrictions on physical, emotional and social functioning of children and adolescents.Objectives:The aim of this study was to determine the impact of acceptance and commitment therapy (ACT) on perceived stress and special health self-efficacy in seven to fifteen-year-old children with DM.Patients and Methods:The present study was a clinical trial with a pretest-posttest control group design. The study population included all seven to fifteen-year-old patients who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…The changes in the control group showed that the mean was 47.94 in the pre-test, 47.87 in the Post-test, and47.86 in the follow-up. This finding is consistent with the studies of Lappalainen et.al [26] Moazzezi et al [27], and Clarke et al [28].…”
Section: Discussionsupporting
confidence: 93%
“…The changes in the control group showed that the mean was 47.94 in the pre-test, 47.87 in the Post-test, and47.86 in the follow-up. This finding is consistent with the studies of Lappalainen et.al [26] Moazzezi et al [27], and Clarke et al [28].…”
Section: Discussionsupporting
confidence: 93%
“…One of the three studies that measured diabetes self-management found a significant increase post-intervention [63]. In addition, one study found a significant increase in a composite of nutrition, exercise, and alcohol self-efficacy post-intervention [65]. …”
Section: Resultsmentioning
confidence: 99%
“…In two studies by Behrouz et al 29 and Amsberg et al, 40 the use of ACT was effective on the reduction of the symptoms of depression, anxiety and stress. In addition, ACT impacted hopelessness in the study by Sahebari et al 41 and perceived stress and selfefficacy in the study by Moazzezi et al 42 The commitment to use emotional control, adherence to behavioral commitment, clarification of values and doing behaviors that are consistent with values that accompany expression of metaphors, defusion and acceptance during ACT can be effective in improving diabetes-related emotional distress. In this regard, the patients are helped to accept their thoughts and feelings and be committed to changes in their thoughts or behaviors.…”
Section: Discussionmentioning
confidence: 97%